The effect of iron coating on stabilizing rice direct seeding onto puddled soil on growth and production - Ramli Ramli; Kaimudddin Kaimudddin; Muh Riadi; Burhanuddi Rasyid (Journal of Agriculture and Applied Biology, 2022)
Rice is a food-crop commodity that plays an important role in Indonesia's economy. This research aims to analyze the following aspects: 1) the response of several rice varieties to the growth and production of rice and 2) the effect of iron coating on the growth and production of rice. This study was conducted in Borongloe Village, Bontomarannu District, Gowa Regency, from March to December 2021. The split-plot design was applied for two factors. The main plot was used to test for the first factor, namely variety, for Inpari 32, Cigeulis, and Mekongga, and the subplot was used to test for the second factor, namely coating, uncoating, 25% coating, and 50% coating. The two factors were combined to create 9 treatment combinations. Each treatment combination was repeated four times. The Inpari 32 variety was found to be the best variety for coating based on the number of pithy seeds (82.04 per panicle), the weight of the seeds per panicle (2.50 g), and production (4.04 t h-1). Significant plant height was also seen in the Mekongga variety (121.39 cm). Furthermore, the 25% coating treatment was the best treatment for increasing crop yields based on the character of the number of tillers (24.32 tillers per clump) and the number of productive tillers (19.31 stem).